Menyemai Inspirasi: Membimbing Mahasiswa dalam Perjalanan PKL - Julianto, Pebi (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2024)
Practical Work Experience (PKL) is a crucial stage in higher education that allows students to apply the knowledge they have learned in a real-world context. This article aims to evaluate the implementation of PKL for students of the Faculty of Ushuluddin Adab and Dakwah IAIN Kerinci at KUA Depati Tujuh. The methods used in this study include observation, interviews, and periodic monitoring, focusing on the development and challenges faced by students during their PKL. Important findings indicate that although most students were able to adapt to the work environment, there were several obstacles, such as low levels of discipline and adherence to the instructions given. The results of this service highlight the need for improved communication and coordination between supervising lecturers and students, as well as enhanced pre-PKL training to better prepare students before entering the workforce. The conclusion of this study emphasizes the importance of ongoing support during the PKL period to achieve optimal outcomes while providing recommendations for the future development of the PKL program to make it more effective and beneficial for students.